Insufficient generation of Th17 cells in IL‐23p19‐deficient BALB/c mice protects against progressive cutaneous leishmaniasis. Issue 1 (6th December 2017) - Dietze‐Schwonberg, Kirsten; Lorenz, Beate; Kostka, Susanna Lopez; Schumak, Beatrix; Gessner, André; von Stebut, Esther
Abstract: Healing of leishmaniasis—a parasitic skin disease—is associated with high levels of secreted interferon (IFN)γ and IL‐12 in resistant C57BL/6 mice and humans. Susceptible BALB/c mice predominantly react with a Th17/Th2/Treg‐related immune response and finally succumb to infection. Previously, we showed that BALB/c IL‐17A −/− mice are protected against Leishmania (L.) major infections, indicating that IL‐17A—predominantly produced by Th17 cells—plays an important role for disease outcome. We now investigated DC‐derived cytokines and finally identified IL‐23p19 as key cytokine responsible for induction of Leishmania ‐specific Th17 cells that play an important role for progressive disease in susceptible BALB/c mice.